IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH DALAM MENINGKATKAN KESADARAN MASYARAKAT PADA PENGELOLAAN SAMPAH DI KELURAHAN RAWASARI JAKARTA PUSAT TAHUN 2023 - Patria, Yoka Mai; Firman, Dede (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to analyze the implementation of waste management policy to increase community awareness in Rawasari Village of Central Jakarta. To analyze the obstacles encountered in implementing the waste management policy to increase community awareness on waste management in Rawasari Village of Central Jakarta. To analyze and find out what efforts were made to overcome the obstacles in implementing the waste management policy to increase community awareness on waste management in Rawasari Village of Central Jakarta. The study uses a qualitative approach with a descriptive analytical method. Data were collected through observation, documentation, and interviews, then triangulation method was used for analysis. The results show that the implementation of waste management policies is crucial. Active participation in waste management can increase awareness and concern for the environment. Additionally, government support and cooperation among relevant parties are also essential factors in the success of these policies.